Analysis of the perception of employees regarding good manufacturing practices in a community restaurant (Research, Society and Development, 2022)
The good manufacturing practices are technical sanitary procedures and their harmony with the sanitary legislation is essential for the food to have all the guarantee of its quality. This work aimed to evaluate the hygienic sanitary conditions and the perception that the collaborators have about the hygiene practice in the work environment, employed from the production of the food, to its distribution. This can ensure the quality of the food and, as a result, the health of the diners. From this point on, the training of employees is extremely important to protect the health of consumers. This is a descriptive, cross-sectional study that was carried out with the employees of a community restaurant in the Federal District. The data was collected by applying a Google form in interview format and then analyzed using the Excel program and exposed by tables and graphs with simple arithmetic mean. Through the results obtained, it can be seen that the employees correctly understood about good practices during food handling (92.9%; n=26). It is concluded that proper training in food and nutrition units, as well as the role of the nutritionist are extremely important in food production.